Simultaneous bilateral avascular necrosis of the humerus and femur in long COVID-19: a case report - Mesut Bakır; Şebnem Rumeli (Travmatologiâ i Ortopediâ Rossii)
Background. The COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has prompted the widespread use of corticosteroids as a treatment strategy, particularly in cases of severe pneumonia and cytokine storm. While this therapy has saved countless lives, its side effects have also been well-documented, including the development of avascular necrosis.